The Effect of Health Education on Newborn Care on Knowledge at Home - Wise Polin Sahetapy; Raden Maria Veronika Widiatrilupi (Jurnal Siti Rufaidah, 2025)
Indonesia’s infant mortality rate remains a pressing public health challenge, recorded at 24 per 1,000 live births in 2021. Most infant deaths occur within the first month of life and are preventable through adequate parental knowledge of newborn care. This study aimed to analyze the effect of health education on mothers’ knowledge of newborn care at home. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed. The sample consisted of 30 mothers with newborns aged 0–3 months, selected using purposive sampling. Knowledge was measured using a validated questionnaire before and after health education interventions delivered through counseling and group discussions. Data were analyzed using the Shapiro-Wilk normality test and the Paired T-Test. Results showed that prior to the intervention, 46.7% of mothers had insufficient knowledge, 36.6% had sufficient knowledge, and 16.7% had good knowledge. After the intervention, knowledge improved significantly, with 56.7% achieving good knowledge. The average score increased from 58.40 to 78.60, with a t-value of -9.84 and p = 0.000 (p < 0.05). The findings confirm that health education significantly enhances maternal knowledge of newborn care, supporting efforts to reduce infant mortality in Indonesia through improved home-based practices.